An evaluation of adult safeguarding outcomes' focused recording in the context of Making Safeguarding Personal. Issue 4 (8th August 2016) - Gough, Matthew
Abstract : Purpose: To evaluate the impact in one local authority of Making Safeguarding Personal upon the recording of outcomes in safeguarding interventions. To determine to what extent person centred outcomes were in evidence. Design/methodology/approach: Analysis of data provided by the local authority across adult safeguarding teams informed by a critical theory approach. Findings: There is a need for cultural and system change to fully embed Making Safeguarding Personal principles within local authority safeguarding. This case study identified that practitioner recording was inconsistent with the need for greater recognition of person centred approaches within adult safeguarding. Views of the service user are constructed and moderated by the assessing proofessional and the user voice is seldom evident in recording of safeguarding interventions. Research limitations/implications: This study was wholly reliant upon the data provided rather than primary investigations with practitioners and service users. The focus on recorded data permitted variance and recorded data was open to worker interpretation. Making Safeguarding Personal. The starting premise of the methodology by adopting a critical perspective sought to elevate the perspective of marginalised service user groups. This may have unduly framed the practitioner provider from a deficit position. Practical implications: The need to ensure Making Safeguarding Personal approaches are embedded fully in all aspects of local authority safeguarding. There is a need for recording to greater reflect principles of empowerment with the wishes of service users, their narratives and actual words providing greater weight to assessment. Originality/value: Making Safeguarding Personal is a relatively new development for safeguarding adults and the evidence base is building. This paper focuses on the recorded outputs of safeguarding interventions which complements work already produced which has focused on system and strategic changes.